Upper limb impairments and their impact on activity measures in children with unilateral cerebral palsy - Klingels, K.; Demeyere, I.; Jaspers, E.; De Cock, P.; Molenaers, G.; Boyd, Roslyn; Feys, H. (2012)
Background: Insights in upper limb impairments and their relationship with activity measures in children with unilateral cerebral palsy (CP) are important to optimize treatment interventions. Aims: (1) To investigate upper limb impairments and activity limitations in children with unilateral CP; (2) to compare these according to the Manual Ability Classification System (MACS), timing of lesion (congenital/acquired) and age; (3) to determine the impact of impairments on activity measures. Methods: Eighty-one children with unilateral CP aged 5-15 years (mean 9 years 11 months; congenital N = 69, acquired N = 12) were recruited. Body function measurements included passive range of motion (PROM), muscle tone, strength and sensibility. At activity level, the Melbourne Assessment, Assisting Hand Assessment (AHA) and Abilhand-Kids were assessed. Results: Most PROM limitations were found for elbow extension and supination. Increased tone and weakness were most prominent in distal muscles. Stereognosis and two-point discrimination were mostly affected. Children with a lower MACS level or acquired lesion had significantly more impairments and activity limitations. In children with congenital lesions, best predictors for unimanual capacity (Melbourne Assessment) were wrist strength, stereognosis and proprioception, and for bimanual performance (AHA) wrist strength and grip strength, explaining 76% of the variance. For the Abilhand-Kids, wrist strength and stereognosis predicted 46% of the variance. Conclusions: Classification according to MACS and timing of lesion is important to differentiate within the wide range of impairments and activity limitations. In children with congenital lesions, unimanual capacity and bimanual performance are highly determined by distal strength, supporting the additional use of impairment-based interventions. © 2012 European Paediatric Neurology Society. Published by Elsevier Ltd. All rights reserved.